1986
DOI: 10.1016/0309-1651(86)90037-8
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against nuclear matrix detect nuclear antigens in mammalian, insect and plant cells: An immunofluorescence study

Abstract: We have applied monoclonal antibodies generated against nuclear matrix in an immunofluorescence study of a variety of plant and animal species. Antibodies P1 and I1 detected antigens in all species examined, including higher and lower plants. Antibodies PI1 and PI2 stained only animal cells, and showed some tissue and/or species-specific variability in staining pattern. The presence of similar nuclear matrix components in such diverse species suggests that nuclear order may be maintained by similar mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
6
15
1
Order By: Relevance
“…A number of studies have shown that such an immunofluorescence labeling pattern is produced by pore complex-specific antibodies (Davis and Blobe11986, 1987;Hanover et al 1987;Park et al 1987;Snow et al 1987). The nucleoplasmic labeled patches detected in previous work using PI1 hybridoma culture supernatant, or unpurified PI1 ascites fluid (Chaly et al 1984(Chaly et al , 1986 were not observed in this study. The loss of internal nuclear labeling in PI1 antibody fractionated on an hydroxylapatite column is being investigated.…”
Section: Characterization and Localization Of The Antigen Recognized contrasting
confidence: 94%
See 2 more Smart Citations
“…A number of studies have shown that such an immunofluorescence labeling pattern is produced by pore complex-specific antibodies (Davis and Blobe11986, 1987;Hanover et al 1987;Park et al 1987;Snow et al 1987). The nucleoplasmic labeled patches detected in previous work using PI1 hybridoma culture supernatant, or unpurified PI1 ascites fluid (Chaly et al 1984(Chaly et al , 1986 were not observed in this study. The loss of internal nuclear labeling in PI1 antibody fractionated on an hydroxylapatite column is being investigated.…”
Section: Characterization and Localization Of The Antigen Recognized contrasting
confidence: 94%
“…3 a). A similar pattern of fluorescence at the nuclear periphery had been noted when other mammalian cells and insect cells were analyzed with the same antibody (Chaly et al 1984(Chaly et al , 1986. A number of studies have shown that such an immunofluorescence labeling pattern is produced by pore complex-specific antibodies (Davis and Blobe11986, 1987;Hanover et al 1987;Park et al 1987;Snow et al 1987).…”
Section: Characterization and Localization Of The Antigen Recognized supporting
confidence: 59%
See 1 more Smart Citation
“…6B) and FS-4 (Fig. 6E) cells and is typical of nuclear matrix-associated and hnRNP antigens (16,36). Little, if any, hnRNP C staining was observed in the cytoplasm of either cell type.…”
Section: Resultsmentioning
confidence: 92%
“…Among the WGA-binding pore complex glycoproteins of Xenopus oocytes we have recently identified a major component of Mr 68,000 (p68) which is confined to the pore channel and crucially involved in nuclear protein transport processes (Dabauvalle et al 1988 b; see also Featherstone et al 1988). This pore complex glycoprotein is evolutionarily highly conserved and has been detected in a variety of species ranging from insects to mammals by means ofimmunofluorescence and immunoblotting studies employing the monoclonal antibody Pl1 (Chaly et al 1984(Chaly et al , 1986Benavente et al 1989 a, b;Dabauvalle et al 1988 b). Furthermore, microinjection of antibody PI1 inhibited nuclear protein uptake not only in Xenopus oocytes (Dabauvalle et al 1988 b) but also in mammalian cells (Benavente et al 1989 a, b).…”
Section: Introductionmentioning
confidence: 99%